Combining Sanford Arylations on Benzodiazepines with the Nuisance Effect. Issue 18 (2nd August 2017) - Khan, Raysa; Boonseng, Sarote; Kemmitt, Paul D.; Felix, Robert; Coles, Simon J.; Tizzard, Graham J.; Williams, Gareth; Simmonds, Olivia; Harvey, Jessica‐Lily; Atack, John; Cox, Hazel; Spencer, John
Abstract: 5‐Phenyl‐1, 3‐dihydro‐ 2H ‐1, 4‐benzodiazepin‐2‐ones react under palladium‐ and visible light photoredox catalysis, in refluxing methanol, with aryldiazonium salts to afford the respective 5‐(2‐arylphenyl) analogues. With 2‐ or 4‐fluorobenzenediazonium derivatives, both fluoroaryl‐ and methoxyaryl‐ products were obtained, the latter resulting from a SN Ar on the fluorobenzenediazonium salt ("nuisance effect"). A computational DFT analysis of the palladium‐catalysed and the palladium/ruthenium‐photocalysed mechanism for the functionalization of benzodiazepines indicated that, in the presence of the photocatalyst, the reaction proceeds via a low‐energy SET pathway avoiding the high‐energy oxidative addition step in the palladium‐only catalysed reaction pathway. Abstract :